Galactose transport systems in Streptococcus lactis. - Thompson, J (1980)
Galactose-grown cells of Streptococcus lactis ML3 have the capacity to transport the growth sugar by two separate systems: (i) the phosphoenolpyruvate-dependent phosphotransferase system and (ii) an adenosine 5'-triphosphate-energized permease system. Proton-conducting uncouplers (tetrachlorosalicylanilide and carbonyl cyanide-m-chlorophenyl hydrazone) inhibited galactose uptake by the permease system, but had no effect on phosphotransferase activity. Inhibition and efflux experiments conducted using beta-galactoside analogs showed that the galactose permease had a high affinity for galactose, methyl-beta-D-thiogalactopyranoside, and methyl-beta-D-galactopyranoside, but possessed little or no affinity for glucose and lactose. The spatial configurations of hydroxyl groups at C-2, C-4, and C-6 were structurally important in facilitating interaction between the carrier and the sugar analog. Iodoacetate had no inhibitory effect on accumulation of galactose, methyl-beta-D-thiogalactopyranoside, or lactose via the phosphotransferase system. However, after exposure of the cells to p-chloromercuribenzoate, phosphoenolpyruvate-dependent uptake of lactose and methyl-beta-D-thiogalactopyranoside were reduced by 75 and 100%, respectively, whereas galactose phosphotransferase activity remained unchanged. The independent kinetic analysis of each transport system was achieved by the selective generation of the appropriate energy source (adenosine 5'-triphosphate or phosphoenolpyruvate) in vivo. The maximum rates of galactose transport by the two systems were similar, but the permease system exhibited a 10-fold greater affinity for sugar than did the phosphotransferase system.